Risk Assessment of Electroconvulsive Therapy in Clinical Routine: A 3-Year Analysis of Life-Threatening Events in More Than 3,000 Treatment Sessions - Hajak, Vivien L.; Hajak, Göran; Ziegelmayer, Christoph; Grimm, Simone; Trapp, Wolfgang (Frontiers in Psychology, 2021)
Background: Extensive research has reported that electroconvulsive therapy (ECT) can be highly effective in approximately 80% of patients suffering from depression. Its clinical use is mainly limited by historical objections and the concern about unwanted adverse effects (AEs), including serious and potentially life-threatening adverse events (pLTAEs), induced either by ECT or by anesthesia. Objective risk estimation is, therefore, a decisive factor in determining an indication for ECT. Methods: This paper presents a retrospective analysis of 3-year safety protocols and patient files of 157 patients who received a total of 3,106 ECT applications in a psychiatric inpatient setting at a psychiatric community hospital. This patient group comprises 5.3% of inpatients admitted with comparable diagnoses. Adverse events were analyzed from standardized safety protocols and patient files with a focus on pLTAEs. Results: Adverse events were reported for 30 (19.1%) of the 157 participants during 39 (6.1%) of 641 hospital stays. Serious pLTAEs occurred during three electroconvulsive stimulations in three patients, who needed action through the administration of medication or mechanical respiration. No patient suffered permanent damage to health, and no patient died. The incidence of these and other AEs was independent of sex, age, and diagnosis of patients, and anesthesia medication. Minor AEs occurred more often with higher stimulus doses and an increasing number of treatments. Conclusion: The low incidence rate of 0.097% of serious pLTAEs that require medical action may allow the conclusion that ECT is a rather safe treatment when performed in a controlled setting. The beneficial risk profile of ECT performed in the standard care of psychiatric hospitals suggests a more generous indication of this treatment method. We recommend that ECT facilities collect individual safety data to allow a reliable judgment of their institutional ECT risk profile.